Interest Rates and Macroeconomic Investment under Uncertainty - Ansgar Belke; Matthias Göcke (Credit and Capital Markets – Kredit und Kapital, 2021)
The interest rate is generally considered as an important driver of macroeconomic investment characterised by a particular form of path dependency, "hysteresis". At the same time, the interest rate channel is a central ingredient of monetary policy transmission. In this context, we shed light on the issue (which currently is a matter of concern for many central banks) whether uncertainty over future interest rates at the zero lower bound hampers monetary policy transmission. As an innovation we derive the exact shape of the "hysteretic" impact of rate changes on macroeconomic investment under different sorts of uncertainty. Starting with hysteresis effects on the micro level, we apply an adequate aggregation procedure to derive the interest rate effects on a macro level. Our results may serve as a guideline for future central banks' policies on how to stimulate investment in times of low or even zero interest rates and uncertainty.
Keywords: E22; E44; C61; 330; Forward guidance; interest rate; investment; monetary policy; path-dependence; hysteresis; uncertainty; zero lower bound